Strategi Rantai Pasok Sayuran Organik Berbasis Petani di Kecamatan Pangalengan, Kabupaten Bandung - Siti Kipdiyah; Musa Hubeis; Budi Suharjo (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2013)
Healthy lifesyle with the slogan “Back to Nature” has become a new trend of the society. Directorate of Processing and Marketing, Ministry of Agriculture in Indonesia has initiated the program "Go Organic 2010" to improve the quality of life and the natural environment of Indonesia and to encourage the development of organic farming and sustainable competitiveness. Supply Chain Management (SCM) has represented overall management of agricultural activities which involved of processing, distribution, marketing, until the desired product to consumer. The Objectives of study included: (1) Identify the characteristics of the vegetables, the supply chain actors, and descriptive analysis of the environmental conditions in Pangalengan; (2) Identify internal and external factors; (3) The formulation of the strategy with the matrix SWOT; (4) Selection of priority strategy. The data was collected through purposive sampling technique which involving 10 respondents and 3 experts. The data used was primary and secondary data by direct interviews, questionnaires and literature study. Selection of strategic alternatives conducted using AHP. The result showed that the supply chain actors of vegetables in Pangalengan were seed suppliers, farmers, traders/collectors, the company, the seller/exporter, foreign markets, traditional market and retail/supermarket. The study showed that the safety of vegetables to consumer (score 0.336) was the main strength and the main weakness organic farming in Pangalengan was limited of financial (score 0.127). Futhermore, supporting of government was the major opportunity (score 0.127) and the major threat was uncertain of climate and weather which affected in production (score 0.144). Based on the formulation of strategic, the study obtained 7 strategy. The first and the second priority strategic related of the marketing, were expanding market/distribution to bussines partnerships (score 0.205) and researching of development in the organic vegetable’s market (score 0.180). The third alternative strategic was supporting of government (score 0.157) which retaled to supervision strategy. Moreover, the fourth and the fifth alternatives related to strategy of financial, were monitoring and overseeing prices (0.156) then strengthening of financial aspects (score 0.114). The sixth and the seventh alternatives related to production management strategy, were planning a better farming (0.107) and improving the quality, quantity and continuity of production (score 0.081).